Behavior of Operative Site Infections in Post-Cesarean Section of the Caribbean Regional Police Clinic In 2022 - Carlos Andrés Delgado Guerrero; Luis Hermes Delgado Guerrero; Estefany Zenith Bula Gómez; Vanesa Madrid Velásquez; Diana Milena Montaño Fuentes (International Journal of Medical Toxicology and Legal Medicine, 2024)
Despite advances in science and technology, postpartum infections remain a significant public health challenge due to their high prevalence and complications associated with morbidity and mortality. Operative Site Infections (ISO) are the most prevalent among hospitalized patients, surpassed only by Urinary Tract Infections (UTIs). Women who develop an ISO following a caesarean section are five times more likely to require medical attention within 30 days of surgery. The establishment of an active surveillance system for post-cesarean women is imperative to identify and manage these cases in a timely manner. The quality of postoperative care, measured through infection rates and the identification of possible causes, together with clear prevention strategies, are essential to reduce the morbidity and mortality associated with ISOs.